Case Report: Solitary metastasis to the appendix after curative treatment of HCC - Zhang, Zun-Yi; Wang, Yu-Wei; Zhang, Wei; Zhang, Bi-Xiang (Frontiers in Surgery, 2023)
Liver cancer now is the fourth most common cancer in China. The most important factor of decreasing the overall survival is recurrence. Nearly 40%~70% patients would be detected with intrahepatic or extrahepatic recurrence in 5 years after R0 resection. Intestine is not an usual site for extrahepatic metastasis. Only one case of HCC metastasis to the appendix has been reported so far. Here we report a case of HCC patient who was detected with solitary metastasis to appendix after R0 resection and a brief review on this rare condition.